2014
DOI: 10.32421/juri.v21i2.36
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Sexual Dysfunction Between End-to-End Anastomosis and Buccal Mucosa Graft

Abstract: Objective: The aim of this study was to compare long term follow-up of sexual dysfunction between end-to-end anastomosis or buccal mucosa graft in short segment bulbar urethral stricture. Material & Method: We performed a meta analysis of cohort study. The data sources was MEDLINE from 1980 through 2011. A fixed effects model with Mantel-Haenszel method was used to calculate the pooled Risk Ratio (RRs) and 95% Confidence Interval (CIs). We assessed the heterogeneity by calculating the I2 statistic. All ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(8 citation statements)
references
References 8 publications
3
5
0
Order By: Relevance
“…Yuri et al [37] in a meta-analysis on sexual dysfunction reported results convergent to those from our analysis, with better outcomes in the non-transecting group. However, we excluded five from the six studies appraised in the metaanalysis by Yuri et al [37], as most of them included strictures in different urethral segments and/or post-radiation patients. Moreover, both ED, EjD and penile complications were appraised together.…”
Section: Non-transecɵng Transecɵngsupporting
confidence: 87%
See 4 more Smart Citations
“…Yuri et al [37] in a meta-analysis on sexual dysfunction reported results convergent to those from our analysis, with better outcomes in the non-transecting group. However, we excluded five from the six studies appraised in the metaanalysis by Yuri et al [37], as most of them included strictures in different urethral segments and/or post-radiation patients. Moreover, both ED, EjD and penile complications were appraised together.…”
Section: Non-transecɵng Transecɵngsupporting
confidence: 87%
“…Penile complications-such as penile length shortening, penile curvature, cold glans sensation or decreased glans sensitivity-are mostly caused by loss of corpus spongiosum length after excision and by compromised vascular supply [43]. Yuri et al [37] in a meta-analysis on sexual dysfunction reported results convergent to those from our analysis, with better outcomes in the non-transecting group. However, we excluded five from the six studies appraised in the metaanalysis by Yuri et al [37], as most of them included strictures in different urethral segments and/or post-radiation patients.…”
Section: Non-transecɵng Transecɵngsupporting
confidence: 79%
See 3 more Smart Citations